2002
DOI: 10.1080/01443610220141290
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of the impacted head of the fetus at caesarean section after prolonged obstructed labour: a randomised comparative study of two methods

Abstract: Obstructed labour is a common obstetric complication in Nigeria associated with poor fetal and maternal outcome. Delivery of the fetus at caesarean section is always difficult, especially if the fetal head is impacted in the pelvis. The mode of delivery at caesarean section may occasionally compound the morbidity associated with obstructed labour. The purpose of this study was to examine and compare the morbidity and mortality associated with two methods of delivery of the impacted fetal head at caesarean sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(20 citation statements)
references
References 4 publications
2
17
1
Order By: Relevance
“…This went in line with result of Kaima, et al 2011 [17]. But, in disagreement with Fasubaa et al 2002 who reported a higher postoperative infection rate in form of endometritis in the "push" method compared to reverse breech extraction. It seems logical that passage of the assistant's hand (who mostly is not part of the operating team) into the vagina can never be under sterile conditions, and therefore contamination of the operating field should be anticipated [18].…”
Section: Discussionsupporting
confidence: 81%
“…This went in line with result of Kaima, et al 2011 [17]. But, in disagreement with Fasubaa et al 2002 who reported a higher postoperative infection rate in form of endometritis in the "push" method compared to reverse breech extraction. It seems logical that passage of the assistant's hand (who mostly is not part of the operating team) into the vagina can never be under sterile conditions, and therefore contamination of the operating field should be anticipated [18].…”
Section: Discussionsupporting
confidence: 81%
“…11 Difficult delivery of impacted head may be facilitated by an assistant pushing from below or by using a reverse breech delivery. 12 In this study uterine incision extension as seen in 13.88%, which is slightly higher compared to the other studies may be due to head delivered by assistant pushing from below. 13 This might be because non-descent of the head with major caput and molding formation makes the delivery of the fetal head challenge.…”
Section: Discussioncontrasting
confidence: 57%
“…The pull method was associated with lesser blood loss than the push method (1257 ml versus898 ml) and lesser uterine wound extension (33% versus 11%). Though the incidence of low Apgar scores was lesser in the pull method, there was no increase in neonatal morbidity or death between groups [18]. Levy et al in a study compared both pull and push method.…”
Section: Technique Of Delivering a Deeply Engaged Headmentioning
confidence: 96%